Factor study of some BioKinematic variables of the step of crossing barriers (3 - 6 - 9) in the 110 m run barriers for young runners - Salman, Thaer Dawood; Arkan Hameed, Asst. Inst Zina (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to set a set of BioKinematic variables for the step of crossing barriers (3–6–9) in a 110-meter barrier for young runners. The researchers concluded the study by interpreting and discussing the results that the most important variables must be relied upon when training and selecting runners that got the best saturation on their factors: 1-The first factor which refers to the total distance of the plan to pass the third barrier + the total distance of the plan to pass the ninth barrier + the total distance Plan to cross the sixth barrier. 2-The second factor which refers to the total vertical speed before passing the third barrier + the total vertical speed before the sixth barrier + the total vertical speed before the ninth barrier. 3- The third factor which refers to the time for the total vertical distance before the third barrier + the time for the total vertical distance before the sixth barrier + the time for the total vertical distance before the ninth barrier. 4- The fourth factor which refers to the angular velocity in the first basement of the third barrier + the angular velocity in the first basement of the sixth barrier + the angular velocity in the first basement of the ninth barrier.